2002
DOI: 10.1183/09031936.02.00512001
|View full text |Cite
|
Sign up to set email alerts
|

Particulate matter and lung function growth in children: a 3-yr follow-up study in Austrian schoolchildren

Abstract: The effects of particulate matter v10 mm in diameter (PM10) and other air pollutants on lung function were assessed in 975 schoolchildren, from eight communities in Lower Austria between 1994-1997. In each community, air pollution data were collected. Spirometry was performed twice a year. PM10 concentration (mean concentration between two subsequent lung-function measures in spring and autumn (summer interval) or between autumn and spring (winter interval)) showed a mean value of 17.36 mg?m-3 in the summer in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
62
0
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(71 citation statements)
references
References 35 publications
4
62
0
2
Order By: Relevance
“…Horak et al also followed lung function among schoolchildren for 3 years and reported that long-term exposure to PM 10 had a significant negative effect on lung function, suggesting that an increase in PM 10 levels was linked to a decrease in FEV 1 and mid-expiratory flow between 25% and 75% (MEF 25-75 ). 22 Our study supports the earlier findings. In addition, because exposure data measured hourly were available in this study, we could evaluate lag model over times matched to each subject's lung function indices, an improvement over previous approaches using fixed calendar days.…”
Section: Discussionsupporting
confidence: 83%
“…Horak et al also followed lung function among schoolchildren for 3 years and reported that long-term exposure to PM 10 had a significant negative effect on lung function, suggesting that an increase in PM 10 levels was linked to a decrease in FEV 1 and mid-expiratory flow between 25% and 75% (MEF 25-75 ). 22 Our study supports the earlier findings. In addition, because exposure data measured hourly were available in this study, we could evaluate lag model over times matched to each subject's lung function indices, an improvement over previous approaches using fixed calendar days.…”
Section: Discussionsupporting
confidence: 83%
“…Comparison with other studies Studies in cooperative school children showed a reduction of lung growth upon exposure to particulate matter [1,3]. The present authors found no association between PM10 and lung volume in unsedated sleep, possibly because FRC in infants is dynamically regulated to maintain end-expiratory lung volume above airway closure [19].…”
Section: Methodological Aspectsmentioning
confidence: 38%
“…Both cross-sectional as well as longitudinal studies have clearly shown diminished lung function in children exposed to higher levels of air pollution [1][2][3][4]. A causative association has been suggested in the observation of decreased age-related lung function decline in adults after reduced exposure to air pollution [5].…”
mentioning
confidence: 99%
“…The seminal paper on lung growth and pollution showed adverse effects on lung development in children 10 to 18 years old leading to clinically significant deficits in attained FEV 1 as they reached adulthood. [70] In addition, 2 large paediatric [71,72] and one adult study [73] have identified small deficits in lung function associated with exposure to particulate matter.…”
Section: Page 13 Of 24mentioning
confidence: 99%